Influence of spark timing on the performance and emission characteristics of gasoline–hydrogen-blended high-speed spark-ignition engine. Issue 6 (18th August 2017) - Shivaprasad, K. V.; Chitragar, Parashuram R.; Nayak, Vignesha; Kumar, G. N.
Abstract: This article experimentally investigates the effect of spark timing on performance and emission characteristics of high-speed spark-ignition (SI) engine operated with different hydrogen–gasoline fuel blends. For this purpose, the conventional carbureted SI engine is modified into an electronically controllable engine, wherein an electronically controllable unit was used to control the ignition timings and injection duration of gasoline. The tests were conducted with different spark timings at the wide open throttle position and 3000 rpm engine speed. The experimental results demonstrated that brake mean effective pressure and engine brake thermal efficiency increased first and then decreased with the increase in spark advance. Peak cylinder pressure, temperature and heat release rate were increased until 20% hydrogen addition and with increased spark timings. NO x emissions were continuously increased with the increment in both spark timings and hydrogen addition, whereas hydrocarbon emissions were increased with spark timings but decreased with hydrogen addition. CO emissions were reduced with the increase in spark timing and hydrogen addition.